Mudança na representação mental de adolescentes depressivos em psicoterapia de orientação psicanalítica - Zanatta, Denise (Universidade do Vale do Rio do Sinos, 2009)
The goal of this research project was to investigate aspects of therapeutic change in adolescents with depressive symptoms, focusing on the characteristics of the mental representation of both the self and the object. Two adolescents participated in it: 16-year-old Paula and 15-year-old Éderson, who were analyzed in 24 sessions using Psychotherapy of Psychoanalytic Orientation. The instruments used to analyze the data were Anna Freud’s Developmental Profile (Freud, 1962/1976) and the Object Relations Inventory (ORI) (Gruen & Blatt, 1990). Through ORI the researcher assessed the characteristics the patient’s self and his/her object representations via a semi-structured interview, in which the patient was asked to describe each of the following individuals: mother, father and the patient himself/herself. The results observed in the case of Paula were rudimentary changes of mental representations, but major changes in terms of affections related to her parents, more capacity for empathy, a decrease aggressivenes
Keywords: adolescentes; depressão; mudança terapêutica; psicoterapia de orientação psicanalítica; representação mental; adolescents; depression; psychotherapy of psychoanalytic orientation; therapeutic change; mental representation; Ciências Humanas